Simulation of Tic-Tac-Toe Game using LabVIEW. Issue 1 (November 2020) - Deepa, R; Janani, M; Singh, Ankita
Abstract: Tic-Tac-Toe game is a two player game, in which a circle (O) or a cross (X) will fill the square block with three rows and three columns. There will be switching between the players in the game where each player will be provided a chance to make their move. If one of the two players have marked the same markers horizontally, vertically or diagonally then that particular player would awarded points. LabVIEW is the platform in which the above game is simulated. Tic Tac Toe is a two-player game which can be played using the LabView software. In this program the select function is used for the player to select the marker and the view feature in the program is to place the marker selected by the player in the desired position of that player. After each player makes their move the software will update and scan while it continues for the conditions of the game. Overall, this tic-tac-toe operates with the features of the programme and can be used without security problems.